ANALISIS HASIL KEGIATAN MBKM KEWIRAUSAHAAN: SUSPECT STAINS - Tunjungsari, Hetty Karunia; Jerico, Hernando; Ernesto, Farrel; Heryanto, Jacky; Hardion, Rifaldo (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Tarumanagara, 2024)
The Merdeka Belajar Kampus Merdeka (MBKM) entrepreneurship program aims to develop students' business skills through practical experience. This paper evaluates the outcomes of the MBKM program, focusing on the oversized t-shirt business of the Suspect Stains brand. The methods used include direct observation of business activities and sales analysis. The results show that participation in this program enhances students' understanding of marketing, financial management, and production. Suspect Stains' oversized t-shirts successfully attract consumers through creative designs and high-quality materials, contributing to increased sales. Challenges such as supply chain issues and market competition were also identified. Overall, the MBKM program is effective in equipping students with entrepreneurial skills and knowledge. Recommendations for further development include increased mentor support and access to business networks. ABSTRAK Program Merdeka Belajar Kampus Merdeka (MBKM) kewirausahaan bertujuan mengembangkan keterampilan bisnis mahasiswa melalui praktik langsung. Makalah ini mengevaluasi hasil program MBKM dengan fokus pada bisnis kaos oversize dari merek Suspect Stains. Metode yang digunakan mencakup observasi langsung kegiatan usaha, dan analisis penjualan. Hasilnya, partisipasi dalam program ini meningkatkan pemahaman mahasiswa tentang pemasaran, manajemen keuangan, dan produksi. Kaos oversize Suspect Stains berhasil menarik konsumen melalui desain kreatif dan kualitas bahan yang baik, yang berkontribusi pada peningkatan penjualan. Tantangan seperti pasokan dan persaingan pasar juga teridentifikasi. Secara keseluruhan, program MBKM efektif dalam membekali mahasiswa dengan keterampilan dan pengetahuan kewirausahaan. Rekomendasi untuk pengembangan mencakup peningkatan dukungan mentor dan akses jaringan bisnis.